Metodologi Pendidikan Akhlak dalam Perspektif Al-Qur’an - Syafri, Ulil Amri (Ta’dibuna: Jurnal Pendidikan Islam, 2018)
The process of akhlaq education in education circumstances nowadays was narrative and verbal, the cognitive parts defeated the implementation process. The methodology existed hadn’t have push and preventive effects to students to respond akhlaq education. In Islam perspective, akhlaq related to the teachings and Islam sources itself, revelation. Therefore, attitudes and akhlaq assessments always related to shariah and its rules. Akhlaq in Islam perspective has samawi values that based on Al-Qur’an. Akhlaq could be understood by leaned to the law and five shariah laws: wajib, sunnah, mubah, makruh, haram, because there are the realities of akhlaq.